An algebraic translation task solved by grade 7–9 students. Issue 1 (2nd January 2019) - Sharpe, Sheree T.
ABSTRACT: In this study, the author examined student attempts to translate a verbal problem into an algebraic statement relating two variables, after they had solved an arithmetic question from the same problem. A total of 645 students from New England (U.S.A.) answered the problem on a mathematics assessment administered at the beginning of the school year. Among students who could solve the arithmetic part of the problem, the use of variables in the correct conventional notation appeared from grade 7 and continuously increased through grade 9. These results suggest that there is a relationship between students' arithmetic understanding and translating verbal problems into algebraic statements relating two variables.